La música infantil en el desarrollo del lenguaje en los niños de educación inicial 2 en el Centro de Educación Inicial Amiguitos, parroquia Yaruquies, cantón Riobamba. - López Cuello, Ailyn Nataly (2024)
The purpose of this research was to contribute to the development of oral language through a learning experience that allows children to communicate their experiences, interests and needs. This work is entitled: Children's music in language development on children of initial II at the “Amiguitos” Initial Education Center of the Yaruquíes parish, Riobamba canton. The importance of children's music as a pedagogical tool for linguistic development is emphasized and the problem of the lack of adequate stimulation in this area is raised. The need to better understand the relationship between music and language development in children is mentioned, whose general objective is to promote children's music as a resource for language. With a mixed approach and quasi-experimental design, the methodology includes the implementation of a music corner in the educational center, using observation techniques to collect data on language development before and after musical activities. The results show significant progress in the linguistic development of the children, initially limited in areas such as image association and articulation of phonemes, but who improved in skills such as participation in conversations and identification of initial sounds. The importance of musical activities in improving vocabulary, pronunciation and other cognitive and socio-emotional skills was highlighted. It is concluded that children's music not only improves language, but also promotes creativity, memory, attention, and socialization. The research recommends regularly incorporating music into the educational curriculum and providing adequate training to teachers to maximize the benefits of this pedagogical strategy. Finally, children's music is revealed as a powerful tool for the comprehensive development of children of initial age, demonstrating its effectiveness in educational contexts.